ANALISIS PENGARUH BEBAS BEA MASUK TERHADAP EKSPOR FURNITUR INDONESIA KE AUSTRALIA - Sari, Norma Amalia; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 9 (2024): Vol.13.No.9. SEPTEMBER 2024 [634-685]DO - 10.24843/EEP.2024.v13.i09.p03, 2025)
Furniture is Indonesia's leading export commodity to Australia. However, BPS data shows that the volume of Indonesian furniture exports to Australia is fluctuating and tends to decline. Indonesian Furniture exports are also still unable to compete with products from China, Vietnam, Italy, United States of America and Malaysia. Meanwhile, one of the government's steps in increasing Indonesian exports to Australia is through economic integration in the Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA) scheme by agreeing to eliminate import duties to zero percent for Indonesian exports to Australia. This research aims to analyze the effect of import duty free policy and other economic factors, namely export prices and the Australian Dollar exchange rate on Indonesian furniture exports to Australia in both the short and long term. This analysis uses the Autoregressive Distributed Lag (ARDL) approach model. The estimation results show that simultaneously the import duty free policy, furniture export prices, and the Australian Dollar exchange rate have a significant effect on Indonesian furniture exports to Australia. Partially, in the short and long term the import duty free policy and the Australian Dollar exchange rate do not have a significant effect on Indonesian furniture exports to Australia. Meanwhile, furniture export prices have a positive and significant effect on Indonesian furniture exports to Australia.